Titania nanotubes prepared by rapid breakdown anodization for photocatalytic decolorization of organic dyes under UV and natural solar light - Saima Ali; Henrika Granbohm; Jouko Lahtinen; Simo-Pekka Hannula (Nanoscale Research Letters, 2018)
Abstract Titania nanotube (TNT) powder was prepared by rapid breakdown anodization (RBA) in a perchloric acid electrolyte. The photocatalytic efficiency of the as-prepared and powders annealed at temperatures between 250 and 550 °C was tested under UV and natural sunlight irradiation by decolorization of both anionic and cationic organic dyes, i.e., methyl orange (MO) and rhodamine B (RhB), as model pollutants. The tubular structure of the nanotubes was retained up to 250 °C, while at 350 °C and above, the nanotubes transformed into nanorods and nanoparticles. Depending on the annealing temperature, the TNTs consist of anatase, mixed anatase/brookite, or anatase/rutile phases. The bandgap of the as-prepared nanotubes is 3.04 eV, and it shifts towards the visible light region upon annealing. The X-ray photoelectron spectroscopy (XPS) results show the presence of titania and impurities including chlorine on the surface of the TNTs. The atomic ratio of Ti/O remains unchanged for the annealed TNTs, but the concentration of chlorine decreases with temperature. The photoluminescence (PL) indicate high electron-hole recombination for the as-prepared TNTs, probably due to the residual impurities, low crystallinity, and vacancies in the structure, while the highest photocurrent was observed for the TNT sample annealed at 450 °C. The TNTs induce a small degradation of the dyes under UV light; however, contrary to previous reports, complete decolorization of dyes is observed under sunlight. All TNT samples showed higher decolorization rates under sunlight irradiation than under UV light. The highest reaction rate for the TNT samples was obtained for the as-prepared TNT powder sample under sunlight using RhB (κ 1 = 1.29 h−1). This is attributed to the bandgap, specific surface area and the crystal structure of the nanotubes. The as-prepared TNTs performed most efficiently for decolorization of RhB and outperformed the reference anatase powder under sunlight irradiation. This could be attributed to the abundance of reactive sites, higher specific surface area, and degradation mechanism of RhB. These RBA TNT photocatalyst powders demonstrate a more efficient use of the sunlight spectrum, making them viable for environmental remediation.